Cell-mediated immune response in typhoid immunization in man. - Maslog, Florita Santos (1976)
Cell-mediated immune reponse (CMIR) was followed for 210 days on 30 subjects after a booster dose of vaccine against typhoid fever. The (CMIR) was measured by the simple direct in vitro of LMIT of A.B. Ibrahim and GNV as using the inhibition of linear migration of peripheral blood leukocytes (PBL) by the LIF generated in the presence of specific antigen in capillary tubes. The LMIT by I and V was confirmed to be 90 sensitive and 100 specific when used with the PPD negative (normals) and PPD positive tubercular patients. This study established the induction and production of CMIR following immunization against typhoid fever.
Thesis (MS Public Health, Medical Microbiology)--University of the Philippines Manila.
Keywords: Typhoid fever- -- vaccination; Cellular immunity; Typhoid immunization